2004
DOI: 10.1038/sj.onc.1206925
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p21 partially rescues Mdm4 loss and uncovers an antiproliferative effect of Mdm4 on cell growth

Abstract: Mdm4 (MdmX) is a p53-binding protein that shares structural similarities with Mdm2 and has been proposed to be a negative regulator of p53 function. Like Mdm2, the absence of Mdm4 has recently been found to induce embryonic lethality in mice that is rescued by p53 deletion. Mdm4-null embryos are reduced in size and die at midgestation, and Mdm4-deficient embryos and embryonic fibroblasts displayed reduced rates of cell proliferation. The p53-induced, cyclin-dependent kinase inhibitor p21 is strongly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…Mdm2-deficient embryos display excess numbers of apoptotic cells proceeding the time of embryonic lethality (Chavez-Reyes et al, 2003), whereas Mdm4-deficient embryos and embryonic fibroblasts display a reduction in cell cycling and increased levels of p21 without displaying increased apoptosis in most tissues. Furthermore, deletion of Bax, but not p21, has been reported to modestly delay the embryonic lethality of Mdm2 null embryos (Montes de Oca Luna et al, 1997;Chavez-Reyes et al, 2003), whereas deletion of p21 partially rescues Mdm4 null mice (Steinman et al, 2004). These results suggest that Mdm2 specifically regulates p53-mediated cell death and Mdm4 specifically regulates p53-mediated inhibition of cell growth during development.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Mdm2-deficient embryos display excess numbers of apoptotic cells proceeding the time of embryonic lethality (Chavez-Reyes et al, 2003), whereas Mdm4-deficient embryos and embryonic fibroblasts display a reduction in cell cycling and increased levels of p21 without displaying increased apoptosis in most tissues. Furthermore, deletion of Bax, but not p21, has been reported to modestly delay the embryonic lethality of Mdm2 null embryos (Montes de Oca Luna et al, 1997;Chavez-Reyes et al, 2003), whereas deletion of p21 partially rescues Mdm4 null mice (Steinman et al, 2004). These results suggest that Mdm2 specifically regulates p53-mediated cell death and Mdm4 specifically regulates p53-mediated inhibition of cell growth during development.…”
supporting
confidence: 52%
“…We have previously reported that deletion of p21 partially rescues Mdm4-null mice (Steinman et al, 2004), and that haploinsufficiency of Mdm4 increases the rate of cell proliferation of p21-null MEFs. These results indicate that Mdm4 has an antiproliferative effect on cell growth when p53 is functionally compromised, either by the absence of p21 or when Mdm2 is overexpressed.…”
mentioning
confidence: 99%
“…A reduction in p21 levels alongside altered p53 expression has also been observed in human hepatocellular carcinomas (36). Reduced p21 expression could also explain the partial rescue of the Mdm4 phenotype, as Mdm4 −/− p21 −/− embryos have a similar phenotype to that seen in the Mdm4 −/− p53 312A/+ mice (37). However, the number of genes whose expression varies between p53 WT and p53 312A/A mice (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, the elevation of Cdkn1a in Brca1-or Mdm4-deficient mice has been observed (Hakem et al, 1996;Migliorini et al, 2002), and, importantly, intercrossing with Cdkn1a-deficient mice partially rescued the phenotype, suggesting that the aberrant expression of Cdkn1a is a major, but not exclusive, reason for the embryonic death Steinman et al, 2004). Interestingly, the phenotype of histone deacetylase 1 (Hdac1)-deficient mice was similar, although more severe, than with Jmjd5 / mice.…”
Section: Jmjd5 Neo/neomentioning
confidence: 87%